News from IMO - Krilić, Tatjana (Transactions on Maritime Science, 2014)
The paper presents current work of selected IMO bodies in the period preceding the publication of this issue of ToMS. The outcome of 28th session of the Assembly in relation to safety and environment protection has been covered, aiming at informing seafarers and shipping industry at large on the decisions taken, as well as on the IMO instruments and/or their amendments that have entered into force.